Job stress, occupational position and gender as factors differentiating workplace bullying experience - Marcin Drabek; Dorota Merecz (Nofer Institute of Occupational Medicine, 2013)
Background: The results of our research broaden the knowledge concerning the correlates of mobbing. The study is aimed at finding out whether an employee's gender, his/her occupational position and level of occupational stress are related to bullying experience. Material and Methods: 1313 employees of a transport company participated in the study. The relationships between gender, occupational position, the level of stress and bullying were analysed. Bullying was measured by the use of the MDM Questionnaire, while work environment was assessed using the Subjective Assessment of Work Questionnaire. Results: It was found that women were generally more exposed to bullying than men (Z = -1.999; p < 0.05). Women experienced more bullying by their colleagues than men did (Z = -2.712; p < 0.01), in particular: bullying by colleagues that destroys the worker's image (Z = -2.922; p < 0.01) and bullying by colleagues that destroys social relations (Z = -3.004; p < 0.01). Individuals with managerial jobs experienced overall bullying (Z = -2.762; p < 0.01), bullying by colleagues (Z = -0.014; p < 0.05) and bullying by colleagues that destroys social relations (Z = -2.260; p < 0.05) more often than the individuals with non-management positions. The results of the study also indicated that employees with higher level of stress in comparison with less stressed co-workers reported more incidents of bullying behaviour (overall bullying - Z = -8.171; p < 0.001, bullying by colleagues - Z = -7.114; p < 0.001, bullying by supervisors - Z = -6.716; p < 0.001, all types of behaviour - p < 0.001). Conclusions: Comparing the results of our study to the previous research, it seems that the pattern of relationships between individual characteristics and bullying is rooted in the wider cultural context, the specificity of the company, its organisational culture as well as its situation. Therefore it's difficult to talk about irrefutable individual correlates of bullying at work. Med Pr 2013;64(3):283-296